2019
DOI: 10.1021/acs.biochem.8b01316
|View full text |Cite
|
Sign up to set email alerts
|

A Central Region of NF-κB Essential Modulator Is Required for IKKβ-Induced Conformational Change and for Signal Propagation

Abstract: NF-κB essential modulator (NEMO) regulates NF-κB signaling by acting as a scaffold for the kinase IKKβ to direct its activity toward the NF-κB inhibitor, IκBα. Here, we show that a highly conserved central region of NEMO termed the intervening domain (IVD, amino acids 112−195) plays a key role in NEMO function. We determined a structural model of full-length NEMO by small-angle X-ray scattering and show that full-length, wild-type NEMO becomes more compact upon binding of a peptide comprising the NEMO binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(45 citation statements)
references
References 66 publications
14
31
0
Order By: Relevance
“…Re-expression of NEMO proteins with mutations that are found in some human disease patients has variable abilities to restore TNFα-induced phosphorylation of IκBα: mutants D113N, R123W, and Q183H were not statistically different than wild-type NEMO, whereas mutants L153R, R173G and R175P had statistically reduced activity as compared to wild-type NEMO (Fig 3C). Consistent with our previous results [22], expression of a NEMO mutant (9-SG) with an insertion in a core domain of NEMO did not restore TNFα-induced phosphorylation of IκBα (Fig 3C). Taken together, these results indicate that clone 1 cells are specifically defective for stimulus-based activation of canonical NF-κB signaling, and that TNFα-induced activation of NF-κB signaling in clone 1 cells can be restored by re-expression of wild-type NEMO.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Re-expression of NEMO proteins with mutations that are found in some human disease patients has variable abilities to restore TNFα-induced phosphorylation of IκBα: mutants D113N, R123W, and Q183H were not statistically different than wild-type NEMO, whereas mutants L153R, R173G and R175P had statistically reduced activity as compared to wild-type NEMO (Fig 3C). Consistent with our previous results [22], expression of a NEMO mutant (9-SG) with an insertion in a core domain of NEMO did not restore TNFα-induced phosphorylation of IκBα (Fig 3C). Taken together, these results indicate that clone 1 cells are specifically defective for stimulus-based activation of canonical NF-κB signaling, and that TNFα-induced activation of NF-κB signaling in clone 1 cells can be restored by re-expression of wild-type NEMO.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the ability of transfected NEMO mutants to support TNFα-induced phosphorylation of IκBα was consistent with their reported activities from previous papers. That is, mutants 9-SG, L153R, R173G, and R175P showed limited activity in 1.1 cells and in previous reports [22, 36, 37, 38], whereas mutants D113N, R123W, and Q183H were nearly as active as wild-type NEMO in both 1.1 cells and previous reports [39].…”
Section: Discussionsupporting
confidence: 66%
“…For example, the N-terminal KBD of NEMO binds the IKK2 NBD to form IKK 2 –NEMO 2 heterotetramers in solution. The central Ub-binding CC2 domain of NEMO, which spans residues 259 to 360, can form homodimers on its own, though a NEMO fragment containing both the CC2 and contiguous regions destabilizes CC2 homodimerization suggesting that neighboring portions of NEMO may antagonize dimerization of one another ( 40 , 41 ). Located C-terminal to the CC2 domain of NEMO is the polypeptide sequence QRRSPP (amino acid residues 384–389) that we have identified as mediating the linear poly-Ub–dependent second interaction between NEMO and IKK2.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ubiquitin (primarily M1-linear ubiquitin) binds to the UBAN domain of NEMO (aa 289–320) ( 39 ). Due to its propensity to aggregate when expressed in bacteria, a crystal structure of full-length NEMO has yet to be solved; however, analytical ultracentrifugation of NEMO aa 1 to 355 ( 40 ) and SAXS of full-length NEMO in solution ( 41 ) have shown that unliganded NEMO is an extended coiled coil ( Fig. 3 , A and B ), suggesting that NEMO must undergo structural rearrangement to bring N-terminally bound IKK and C-terminally bound IκB into proximity for the phosphorylation of IκB.…”
Section: Conformational Changes In Four Well-known Scaffold Proteinsmentioning
confidence: 99%
“…3 A ). For example, biophysical studies of full-length NEMO indicate that NEMO undergoes conformational changes following binding to IKKβ or linear ubiquitin ( 41 , 42 , 43 ). Specifically, it has been shown through 8-anilinonaphthalene-1-sulfonic acid/tryptophan fluorescence emission that incubation of NEMO with IκB and long ubiquitin chains induces a shift in emission of NEMO that is consistent with solvent exposure of hydrophobic residues ( 43 ).…”
Section: Conformational Changes In Four Well-known Scaffold Proteinsmentioning
confidence: 99%